Profile and Clinical Outcome Lateral Condyle Humerus Fracture in Children’s Patients in National Orthopedic Hospital (2022-2024) - Hendra Cahya Kumara; Khrisna Purwa Satyaksa (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2026)
The lateral condyle fracture is the second most prevalent elbow fracture in pediatric populations. Fractures of the distal humerus present challenges regarding diagnosis, treatment, and associated complications. This study aimed to describe the demographic characteristics, treatment modalities, and radiologic outcomes of pediatric lateral condyle humerus fractures managed at Prof. Soeharso Hospital between January 2022 to July 2024. This was a descriptive, retrospective study of pediatric patients diagnosed with lateral condylar humerus fractures during the study period. Patients were classified according to sex, age, treatment method, and outcomes. Data were obtained from hospital medical records and analyzed using Microsoft Excel. Between January 2022 and July 2024, 23 pediatric patients were identified, consisting of 15 boys and 8 girls. The majority of patients (n = 12, 52.2%) were aged 6–10 years. Most patients (n = 21) underwent surgical treatment, while two were treated conservatively. All surgical cases were managed with open reduction and internal fixation (ORIF): 20 patients with 2–3 Kirschner wires and one with a screw. Follow-up radiographs at 6–12 months postoperatively showed bone union in 15 patients, malunion in five, and nonunion in one. Among the conservatively treated patients, one developed a malunion and one a nonunion. In conclusion, pediatric patients treated at Prof. Dr. R. Soeharso Orthopaedic Hospital with open reduction and internal fixation achieved satisfactory union rates and remain the preferred technique for managing displaced lateral condyle fractures in children.